Environmental Coalitions and the Limits of Science: Wilderness Advocacy in Ontario during the 1970s - Warecki, George (Ontario History)

(untitled) (The Ontario Historical Society, 2017)
This article examines the origins, evolution, ideology, and political impact of an environmental coalition in the 1970s. Two wilderness activists in northwestern Ontario challenged established preservationist groups to shift their advocacy from public battles over management policy for individual parks, to design and promote a system of provincially-owned wilderness parks. To build public support and maximize their political clout, the two advocates persuaded five groups to form the Coalition For Wilderness (CFW) in 1973. Unfortunately CFW was mostly a two-man show. Constituent groups gave insufficient material support because of their diverse interests, economic woes, and the “free rider” problem. Nevertheless, CFW’s tactic of privately lobbying park planners within the Ontario Ministry of Natural Resources had some political impact. It generated policy information and educated the public about the need for a wilderness park system, thereby supporting the parallel efforts of the bureaucrats. Ironically, the coalition’s scientific rationale for protecting wilderness limited its influence among planners and the wider advocacy community, both of whom regarded recreational and other reasons for wilderness protection as more politically defensible than science. This difficult episode taught the CFW leadership valuable lessons, enabling Ontario preservationists to build more successful coalitions in the 1980s and 1990s.